miRNA-125a-5p inhibits hepatocellular carcinoma cell proliferation and induces apoptosis by targeting TP53 regulated inhibitor of apoptosis 1 and Bcl-2-like-2 protein - Ming, Ma (Exp Ther Med, 2019)
The present study aimed to investigate the role and underlying molecular mechanism of microRNA (miR)-125a-5p in hepatocellular carcinoma. The level of miR-125a-5p was detected using reverse transcription-quantitative polymerase chain reaction. TargetScan was used to investigate the association between miR-125a-5p and TP53-regulated inhibitor of apoptosis 1 (TRIAP1)/B cell lymphoma-2-like 2 protein (BCL2L2). Dual luciferase reporter assay was used to confirm this prediction. To investigate the role of miR-125a-5p in hepatocellular carcinoma (HCC) cells, miR-125a-5p was overexpressed in the human HCC cell line PLC/PRF/5 using miR-125a-5p mimics. Subsequently, cell proliferation, cell apoptosis and cell migration were studied using MTT assay, flow cytometry analysis and Transwell assay, respectively. Protein expression levels in the present study were measured by western blot analysis. Taken together, the present results suggested that miR-125a-5p was markedly downregulated in HCC cells. TRIAP1 and BCL2L2 were direct targets of miR-125a-5p and were upregulated in PLC/PRF/5 cells. miR-125a-5p upregulation inhibited PLC/PRF/5 cell viability and migration and induced cell apoptosis. In addition, miR-125a-5p overexpression increased the expression of caspase9 and apoptotic protease-activating factor 1. Notably, the present study revealed that all the effects on PLC/PRF/5 cells elicited by miR-125a-5p overexpression were eliminated by TRIAP1/BCL2L2 upregulation. In conclusion, miR-125a-5p was shown to be downregulated in hepatocellular carcinoma and its upregulation inhibited hepatocellular carcinoma cell growth and metastasis by targeting TRIAP1 and BCL2L2.